Antioxidant and antimicrobial activities of Penicillium sp. lectins - Singh, Ram S.; Walia, Amandeep K. (Archives of Biological Sciences, 2019)
Paper description: The purification and physico-chemical characterization of Penicillium duclauxii, P. proteolyticum and P. griseoroseum lectins has been reported. This is the first report of the antimicrobial and antioxidant potential of lectins from Penicillium sp. The lectins exhibited a moderate antioxidant potential and strong antibacterial action. The current study will help in understanding the implications of Penicillium lectins in the biomedical field. Abstract: Lectins are a diverse group of proteins of non-immune origin that interact specifically with glycans. Owing to their specificity, they can mediate various cellular and molecular recognition processes. To explore information on biological activities of lectins from Penicillium duclauxii, P. proteolyticum and P. griseoroseum, they were investigated for their antioxidant and antimicrobial activities. Penicillium sp. lectins exhibited moderate antioxidant activity. P. duclauxii, P. proteolyticum and P. griseoroseum lectins inhibited DPPH with an IC50 value of 71.42, 75.04 and 82.11 µg/mL, respectively. P. duclauxii, P. proteolyticum and P. griseoroseum lectins inhibited the hydrogen peroxide radical with IC50 values of 198.57, 209.76 and 215.31 µg/mL, respectively. P. duclauxii and P. proteolyticum lectins exhibited potent antibacterial activity against Gram-negative bacteria. P. griseoroseum lectin inhibited only Gram-positive bacteria. Penicillium sp. lectins did not exhibit antifungal activity. The biological potential of Penicillium sp. lectins will help to understand their biomedical applications. This is the first report on the antioxidant and antimicrobial activities of purified lectins from Penicillium sp. https://doi.org/10.2298/ABS190529035S Received: May 29, 2019; Revised: May 31, 2019; Accepted: June 3, 2019; Published online: June 5, 2019 How to cite this article: Singh RS, Walia AK. Antioxidant and antimicrobial activities of Penicillium sp. Lectins. Arch Biol Sci. 2019;71(3):514-24.